Pembuatan Poster Penanggulangan dan Pencegahan Covid-19 di Kelurahan Pabuwaran Banyumas Sebagai Bentuk Bakti Mahasiswa - Abdul Wahid (PT. Gyandharma Global Media, 2025)
Covid-19 in Indonesia has increased significantly, the increase in Covid-19 cases is due to the low level of public awareness of the implementation of correct health protocols, especially in the Banyumas area. One solution that can be applied is to socialize the implementation of correct health protocols using the poster method via social media in Pabuwaran Village, Banyumas. The purpose of the activity of making posters for handling and preventing Covid-19 is to increase public awareness, especially in Pabuwaran Village, Banyumas, to implement health protocols correctly. The methods used are the survey method and the Participatory Rural Appraisal method. The results of this activity can increase public awareness, especially in Pabuwaran Village, of the importance of implementing correct health protocols to prevent Covid-19.